Early patent-publications combinations in the history of science and technology evaluation: The indefatigable teachings of the steam navigation - Mendonça, S. (BIOGRAPHICAL AND INTELLECTUAL HISTORY OF SCIENCE, TECHNOLOGY AND INNOVATION, 2017)
Early uses of patent and publications as complementary partial indicators of technical progress have so far been an under-exploited source of methodological guidance for contemporary professional practice, policy analysis and academic research. This paper documents a pioneering instance in which publications and patents were used to chart the course of a breakthrough technology. In the mid-19th century Bennet Woodcroft, the founder of the Science Museum in London, tried to make sense of the trends and turns of steam navigation, which was then on the verge of its take-off. This paper addresses the issue of how his Sketch of the Origin and Progress of Steam Navigation can be considered an early example of conscientious deployment of both publications and patents as partial, but complementary, indicators of innovation. We argue that his 1848 book compensates for the long cycle of development of complex technologies by using the historical method and for the uncertainty of the actual developments by triangulating contrasting bodies of evidence. We conclude that his “belts-and-suspenders” approach proved robust, as modern steamship historiography is in accordance with many of the stylised facts and salient features he identified and described